A Prospective Longitudinal Study of Family From Generation to Generation. (October 2018) - Bell, Linda G.
This study explores the effects of family system characteristics on the children's families when they grow up and become parents themselves. Family systems have profound effects for individual family members. The study addresses the question of whether or not these effects continue into the next generation by influencing the families created by adult children. Also evaluated is the extent to which parental intentions to make specific changes can be successful. Families in two generations participated in home interviews during the midlife/adolescent family life cycle stage. During home interviews at both waves, family members completed a questionnaire describing their family. They then discussed differences of opinion about the family and jointly created a projective "picture" of their family. Both family members' reports and coded measures from the family interaction process supported a continuity between family of origin (FoO) characteristics and the next generation's families. Evidence was also found for the ability of both mothers and fathers to purposely change particular family characteristics, such as connection, individuation, or conflict, in their second generation families. These results support the usefulness of exploring connections between FoOs and families of procreation. They also suggest that helping parents focus on particular characteristics they wish to change from their FoOs may enhance their success in making those changes.